Consolidation of water management and efficiency parameters for development of green building rating system - Mohammed Usman, Abdullahi; Abdullah, Kamil (Zes Rokman Resources, 2018)
Water generation and distribution involve activities that leads to energy consumptions in various ways. This leads to GHG emission which make it important for various sustainable development assessment. Hence it is important to develop some consolidated parameters to cover water in building life cycle assessment (LCA). Development of rating system involves the utilisation of some parameters and points allocation. These parameters and points allocation varies between countries and their rating systems. This study aim at reviewing water management and efficiency category and the extent of parameters and points allocation across some rating systems. The purpose of the review is to develop a consolidated parameters that will universally cover building life cycle assessment. Eleven rating scheme’s categories, parameters and points allocation were reviewed. Specifically, water generation, distribution and usage was further elaborated for this study. The parameters were reviewed from the context of their, adaptability, preference, prevalence, relevance and measurability of parameter to suit the universal concept of sustainable building assessment. The review shows that the variations of the parameters and points distribution are based on social, economic and environmental need of the country. The highest parameters and points allocation signifies the need of efficient water generation, distribution and usage and lack of enough fresh water for daily activities. The lowest consideration is due to advancement in sustainable water generation, distribution and usage. The study consolidated the parameters in to nine parameters covering the strategies for reducing unnecessary water usage and other sourcing consequences. They also cover the approximate accounting of GHG emission from water consumption and its reduction. The study can be used by researcher, organisations and countries developing rating schemes. As the study harmonised parameters covered the entire sustainable building and greenhouse gas assessment in term of water generation, distribution and usage.